ChemInform Abstract: A Practical Synthesis of Azobenzenes Through Oxidative Dimerization of Aromatic Amines Using tert‐Butyl Hypoiodite. Issue 31 (11th July 2013) - Takeda, Youhei; Okumura, Sota; Minakata, Satoshi
Abstract A convenient method with an excess of tBuOCl and NaI is developed to give various symmetrical azobenzenes in good yields.